Culturally Contextualized Simple Biotechnology Learning Through Ethnopedagogy: A Qualitative Case Study in Siem Reap, Cambodia - Wahyu Wido Sari (Universitas Pahlawan Tuanku Tambusai, 2026)
Science learning is often perceived as requiring laboratory facilities and sophisticated equipment, creating barriers for schools with limited educational resources. The aims of this study to explore the implementation of a simple biotechnology learning activity utilizing locally available plant materials in a school in Siem Reap, Cambodia. While previous studies have emphasized biotechnology learning through laboratory-based approaches, limited research has examined how simple biotechnology activities can be integrated with ethnopedagogical principles to promote culturally responsive science learning. This study employed a qualitative descriptive case study approach using student-generated drawings, classroom observations, and visual documentation as data sources. The findings showed that students actively engaged in scientific exploration through flower pigment transfer activities using local plant materials. Students incorporated culturally meaningful symbols, including Angkor Wat, lotus flowers, traditional Cambodian houses, durian fruit, and local floral motifs, into their artwork. The activity stimulated creativity, strengthened sensory engagement, and encouraged students to connect scientific concepts with local biodiversity and cultural heritage. Furthermore, students demonstrated contextual understanding of natural resources through artistic representations rooted in their everyday experiences. The study concludes that simple activities grounded in local culture can provide meaningful and accessible science learning while strengthening students’ environmental awareness and cultural identity.